2020
DOI: 10.1161/jaha.120.016575
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Revascularization Strategy in Non–ST‐Segment–Elevation Myocardial Infarction With Multivessel Coronary Artery Disease: Culprit‐Only Versus One‐Stage Versus Multistage Revascularization

Abstract: Background Few studies have investigated optimal revascularization strategies in non–ST‐segment–elevation myocardial infarction with multivessel disease. We investigated 3‐year clinical outcomes according to revascularization strategy in patients with non–ST‐segment–elevation myocardial infarction and multivessel disease. Methods and Results This retrospective, observational, multicenter study included patients with non–ST‐segment–elevati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 19 publications
0
24
2
Order By: Relevance
“…Likewise, in patients with NSTEMI, an observational study suggested that multivessel revascularization reduced 3-year rates of major adverse cardiac events (MACE) (total death, MI, any revascularization) compared with culprit-vesselonly revascularization [34]. However, in this study, 1-stage multivessel revascularization was not superior to multistage revascularization except in low-to intermediate risk patients [34].…”
Section: Acute Coronary Syndromescontrasting
confidence: 59%
See 1 more Smart Citation
“…Likewise, in patients with NSTEMI, an observational study suggested that multivessel revascularization reduced 3-year rates of major adverse cardiac events (MACE) (total death, MI, any revascularization) compared with culprit-vesselonly revascularization [34]. However, in this study, 1-stage multivessel revascularization was not superior to multistage revascularization except in low-to intermediate risk patients [34].…”
Section: Acute Coronary Syndromescontrasting
confidence: 59%
“…Several new metaanalyses, including data from the COMPLETE trial, comparing complete vs. culprit-only revascularization in STEMI patients supported the value of complete revascularization to reduce rates of re-infarction, cardiovascular mortality, and repeat revascularization with no difference in all-cause mortality [33]. Likewise, in patients with NSTEMI, an observational study suggested that multivessel revascularization reduced 3-year rates of major adverse cardiac events (MACE) (total death, MI, any revascularization) compared with culprit-vesselonly revascularization [34]. However, in this study, 1-stage multivessel revascularization was not superior to multistage revascularization except in low-to intermediate risk patients [34].…”
Section: Acute Coronary Syndromesmentioning
confidence: 95%
“…Several earlier studies have examined the impact of multivessel PCI on AMI patients with various inclusion criteria, timing of non-culprit vessel PCI, statisticalheterogeneity, endpoints, and conclusions. Because of conflicting results and lack of robust evidence, there is divergent clinical practice (10)(11)(12)(13)(14)(15)(16). Current guidelines suggested that PCI of non-infarct arteries should be considered in STEMI patients with the multivessel disease before hospital discharge, either at the time of primary PCI or as a planned staged procedure (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, another national registry data from Korea found that complete revascularization reduced major adverse cardiac events compared with culprit-only PCI. However, there was no benefit with either immediate multivessel revascularization or staged multivessel revascularization ( 16 ). After risk stratification by the Global Registry of Acute Coronary Events (GRACE) score, immediate multivessel PCI's potential benefit was only found in low-to-intermediate risk NSTEMI patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation